VIDEO LAB REPORTS USING TikTok APPLICATION FOR INORGANIC CHEMISTRY CLASS AT THE FLEXIBLE DIGITAL MODEL FDM AT PREPATEC MORELIA (Proceedings of the International Conference on Education, 2021)
At PrepaTec Morelia, the subject of inorganic chemistry is taught at the third semester of High School, five days a week in 50-minute sessions. Last year we had 129 students’ ages between 16 and 17 years distributed in 4 groups taking the class. Due to the contingency of Covid-19, the class was redesigned to adapt to the virtual model. As part of the class in the face-to-face model, several laboratory practices related to the topics of the course are carried out and the idea was to redesign them as well to the virtual model. Therefore, it was thought of activities that promote the interest of the students so that they develop scientific competencies using technology; after reading the article on the use of TikTok in the classroom, it was decided to use this tool. The idea was to find two fun activities for the students to do at home and to comply with showing a chemical phenomenon and instead of making a written report they were asked to make a video using the TikTok app so that the students would present the conclusions and explanation of these observed phenomena. The two activities that were chosen were: Intermolecular Forces: Magic Trick and Hot Ice with sodium bicarbonate, At the end of the activity the results of the satisfaction survey with grades of 4.76 were obtained with a standard deviation of 0.28 and students seem to be more motivated by doing a video report rather than filling a document with the lab results.
Keywords: Tiktok; Chemistry; Labs; Virtual Education; Educational Innovation; Higher Education